Cognitive-Behavioral Therapy for Insomnia in Older Adults. Issue 1 (February 2022) - Cassidy-Eagle, Erin L.; Siebern, Allison; Chen, Hongtu; Kim, Hyun (Monica); Palesh, Oxana
Highlights: Insomnia in older adults can lead to excess disability and declining health. CBT-I is an evidence-based treatment for those with and without comorbid conditions. Innovative delivery methods and modifications have broadened the reach of CBT-I. Abstract: Sleep is disturbed by a range of factors across the lifespan. However, older adults experiencing disruptions in their sleep are often simultaneously contending with a range of comorbid medical and psychiatric conditions that compound the biological changes in sleep that commonly occur with age. Cognitive behavioral therapy for insomnia (CBT-I) is the gold-standard, nonpharmacological intervention for sleep disturbances, and is a cost-effective treatment approach that can occur in either individual or group format. It has also been shown effective in older adults with medical, psychiatric, and cognitive comorbid disorders. This review highlights the success of CBT-I with older adults, as well as studies that illustrate the use of alternative delivery methods and treatment modifications for complex clinical presentations.